Teachers’ and Students’ Perceptions of Learning Decision-Making and Democratic Participation in School: A Case Study in Catalonia - Gallart, Clara; Castellví, Jordi (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2025)
This case study investigates the perceptions of teachers and students about learning decision-making and democratic participation in their primary education school. This research, conducted at a public school in Barcelona (Catalonia), aims to characterize the opportunities and limitations the studied school provides in this regard, based on the perceptions of 101 students aged 6 to 8 and six of their teachers. Following a qualitative methodology, which included interviews with teachers and a research dossier for the students, the investigation reveals that students perceive that they engage in decision-making within their immediate environment, but show limited awareness of broader, long-term decisions. As inferred from the interviews, teachers appear to significantly influence these processes, since their opinions and beliefs about citizenship and decision-making seem to shape the guidance they provide to students. The findings point out the complexities of learning decision-making and democratic participation in school to foster an active, critical and participative citizenship.